Anaesthetic Management Of Paediatric Patients Undergoing Scoliosis Surgery In Camp (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background Scoliosis is most commonly idiopathic in origin, but it may be congenital or secondary to  neuromuscular disease, trauma, infection or neoplasm.  Aim: Aims of surgery is to correct the curvature, improve posture and reduce progression of  respiratory dysfunction. Objectives: Perioperative challenges for anaesthetist in scoliotic surgery are to avoid hypothermia,  hemodynamic stability, spinal cord monitoring, positioning, induced hypotension, major  blood loss, postoperative pain management and intensive care management of patient. Material and method: After taking parenteral consent, 15 paediatric patient’s data were collected who underwent  scoliotic correction surgery over 12 days from 1st to 12th January of 2019.  Result:Children underwent posterior fusion scoliosis surgery aged (11.2 ± 2.3) years. surgical  duration and blood loss were (7.5 ±1.5) hours, (856 ±235) ml respectively. patients were  shifted to ICU because of prolonged procedure and major fluid shift. Conclusion:  Cardio-respiratory dysfunction may exist as a result of progressive scoliosis or related to  coexisting disease, therefore careful preoperative assessment is required. Intraoperative considerations include the prone position, avoiding hypothermia, minimizing  blood loss and monitoring spinal cord function. Good postoperative pain control is essential and requires a multimodal approach.
Keywords: Anaesthesia, Scoliosis; Spinal cord monitoring; Posterior fusion Introduction